Belief-in and Belief in God - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 1992)
Of all the examples of ‘belief-in’, belief in God is both the most mysterious and the most challenging. Indeed whether and how an apologist can make a case for the intellectual respectability of theistic belief, depends upon the nature of this ‘belief-in’. I shall attempt to elucidate this matter by an analysis of the relation of ‘belief-in’ to ‘belief-that’ and by treating belief in God as a special case of ‘belief-in’.